English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

Not true.

Assume the logs are base a. So log_a(x)= log base a of x.

Then: log_a(n)+1=log(n)+log_a(a) = log_a (n*a).

Now if log_a (n*a)= log_a(n+1), we have that na=n+1 so n(a-1)=1, which means n=1/(a-1). This only happens once for every base a. So the statement is not true for all n.

2007-02-02 05:20:16 · answer #1 · answered by raz 5 · 0 0

Where do you get that from? It's false
log(n+1) = log(n) + 1/n + O(1/n^2)

2007-02-01 12:33:13 · answer #2 · answered by gianlino 7 · 1 0

you can't. It's not so.

proof: let n=9

log(10)<>log(9) + 1

log(9) would have to be zero which it isn't

2007-02-01 12:34:04 · answer #3 · answered by rwbblb46 4 · 0 0

fedest.com, questions and answers